BRAF and epithelial-mesenchymal transition in papillary thyroid carcinoma - challenging the roles of Snail and E-Cadherin? - Mitchell, Brendon; Leone, Dominick; Yang, Shi; Khan, Ashraf; Mahalingam, Meera; Dhingra, Jagdish (American journal of translational research, 2016)
In papillary thyroid carcinoma (PTC), while the role of BRAF is well established, the contribution of BRAF to epithelial-mesenchymal transition is not. To elucidate the relationship between BRAF, surrogates of epithelial-mesenchymal transition (Snail, E-cadherin) and established histopathologic prognosticators in papillary thyroid carcinoma. In this IRB approved cross-sectional study, 50 cases of archived annotated PTC samples were retrieved and immunohistochemically stained for Snail and E-cadherin protein. A semi-quantitative scoring system (incorporating proportion and intensity) was utilized. Snail and E-cadherin expression were noted in 44% and 84% of BRAF mutant and, in 29% and 95% of BRAFWT samples, respectively. No statistically significant correlations were noted between Snail, E-cadherin and histopathologic prognosticators. However, a trend was noted between Snail expression and tumor size <5 cm (P=0.07). Statistically significant differences between BRAF mutant and BRAFWT samples were noted in the following groups: conventional (68% vs. 5%) and tall cell (32% vs. 0%) histopathologic variants, extrathyroidal extension (32% vs. 5%), infiltrative growth pattern (80% vs. 48%), presence of desmoplasia (72% vs. 29%), psammona bodies (48% vs. 10%), and cystic change (32% vs. 5%). Among follicular variant of papillary thyroid carcinoma compared to BRAF mutant samples, BRAFWT samples were more commonly of the encapsulated variety (52% vs. 4%), and microcarcinomas (29% vs. 0%) (P<0.001 and =0.007, respectively). Our findings, supporting the utility of BRAF as a putative therapeutic target in PTC, suggest that the interaction between BRAF and epithelial-mesenchymal transition in papillary thyroid carcinoma is not through induction of the Snail/E-cadherin pathway.